PELAYANAN SISTEM INFORMASI TOKO BESI TUA PADA CV ANEKA LOGAM MELALUI WEBSITE COMPANY PROFILE - Masroy, (2023)
Scrap metal shop is a business that requires good service and high customer trust in order to survive and develop. In the current digital era, the use of technology such as company profile websites is expected to improve customer service at scrap metal shops. This study aims to design an information system using the waterfall method to improve customer service at scrap metal shops through the company profile website. The waterfall method is used to ensure the stages of developing a structured and organized information system. The needs analysis stage is carried out to identify customer service needs and objectives of the scrap metal shop. The design phase is carried out to design an information system and features that will be implemented on the company profile website. The implementation phase involves the development and integration of information systems according to predetermined specifications. This research resulted in the design and development of an information system that is expected to improve customer service at scrap metal shops. Through the company profile website, customers can easily access product information, prices and services offered. Thus, it is expected that the level of customer satisfaction will increase and the trust in scrap metal shops will be stronger